Income and Subjective Financial Well-Being as Determining Factors of Life Satisfaction - Dickason Koekemoer; Z. Munyai; L. S. Ferreira S. J. (Journal of Economics and Behavioral Studies, 2019)
The purpose of the investment is to improve the current level of life satisfaction by achieving investment goals. Investors tend to attain high levels of life satisfaction when their investment goals are achieved and lower levels of life satisfaction when goals are far from achievement. The idiosyncratic characteristics of an individual may often hamper the achievement of investment goals and ultimately influence the level of life satisfaction. These characteristics can either contribute towards low life satisfaction or high life satisfaction. Income and the subjective financial well-being play a determining role in whether an investor has a positive or negative life satisfaction. Hence, the aim of this study was to determine whether income and subjective financial well-being have an influence on the life satisfaction of investors. The results of this study reveal that a strong relationship exists between income, financial well-being, and life satisfaction. Investors who perceived themselves, to have high financial well-being were more likely to have high life satisfaction. On the contrary, investors with low perceived financial well-being were more likely to have low life satisfaction. Similar results were observed for income and life satisfaction since a positive relationship was also found.